Efficacy and effectiveness of 20 child health interventions in China: Systematic review of Chinese literature - Zhang, Jian Shayne F (Journal of global health, 2011)
The research production of the Chinese academics for the past few decades, which is being published in more than nine thousands of Chinese academic periodicals, has recently been digitalized and made available in the public domain. The aim of this study was to systematically identify and assess the evidence from Chinese literature sources on the efficacy and effectiveness of child health interventions in China. The Chinese National Knowledge Infrastructure databases were searched for the studies with primary data on efficacy or effectiveness of child health interventions in China between 1980 and 2011. The searches of PubMed and the 'Lives Saved Tool (LiST)' evidence base were also performed to identify the counterpart evidence in the English language. Of 32 interventions initially identified in the Chinese literature, 20 interventions sustained the primary information addressing efficacy or effectiveness. Among preventive interventions (14 interventions), most studies were dedicated to complementary feeding (7 studies), kangaroo mother care (7 studies) and syphilis detection and treatment (4 studies). Among treatment interventions (6 interventions), the most frequently studied were zinc for treatment of diarrhoea (11 studies) and newborn resuscitation (9 studies). The evidence on efficacy or effectiveness of the 32 interventions conducted in Chinese children in the Chinese literature was either of comparable quality, or more informative than the available reports on China in the English literature, which rarely contained studies on child health intervention effectiveness exclusively in Chinese population. The included studies reported positive results unanimously, implying a likely publication bias. The evidence on the efficacy and effectiveness of child health interventions in China is typically modest in quantity and quality, and implies a notable urban-rural discrepancy in applied health systems research to improve child health interventions and programmes. However, it is clear that considerable research interests and initiatives from both inside and outside the country have been concentrating on implementation, long-term operation, evaluation and further development of child health interventions, especially preventive interventions in China.